Impact of a Workplace Vocal Health Promotion Program on Vocal Doses in College Professors: a Colombian Exploratory Study - Ángela Patricia Atará-Piraquive; Pasquale Bottalico; Lady Catherine Cantor-Cutiva (Revista de Investigación e Innovación en Ciencias de la Salud)
Objective. To determine the effect of a workplace vocal health promotion (WVHP) program on Colombian college professors’ vocal doses. This is an exploratory pre-post-intervention study.